2016
DOI: 10.1002/1873-3468.12052
|View full text |Cite
|
Sign up to set email alerts
|

Transient‐state kinetic analysis of complex formation between photoprotein clytin and GFP from jellyfish Clytia gregaria

Abstract: Luminous organisms use different protein-mediated strategies to modulate light emission color. Here, we report the transient-state kinetic studies of the interaction between photoprotein clytin from Clytia gregaria and its antenna protein, cgreGFP. We propose that cgreGFP forms a transient complex with Ca 2+ -bound clytin before the excited singlet state of the coelenteramide product is formed. From the spectral distribution and donor-acceptor separation distance, we infer that clytin reaction intermediates ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…It was proposed that, upon Ca 2+ binding, clytin adopts a conformation with several orders of magnitude enhanced affinity for cgGFP; then, a very transient complex is formed, in which chemiexcitation of clytin and subsequent energy transfer to cgGFP occur. In other studies, no stable complex of Ca 2+ discharged clytin with cgGFP has been detected, suggesting that such BRET complex must indeed be a short-lived intermediate in the clytin bioluminescence process (54,57).…”
Section: From Natural Bret To Designed Fp-photoprotein Fusionsmentioning
confidence: 84%
“…It was proposed that, upon Ca 2+ binding, clytin adopts a conformation with several orders of magnitude enhanced affinity for cgGFP; then, a very transient complex is formed, in which chemiexcitation of clytin and subsequent energy transfer to cgGFP occur. In other studies, no stable complex of Ca 2+ discharged clytin with cgGFP has been detected, suggesting that such BRET complex must indeed be a short-lived intermediate in the clytin bioluminescence process (54,57).…”
Section: From Natural Bret To Designed Fp-photoprotein Fusionsmentioning
confidence: 84%
“…However, a recombinant aequorin–GFP fusion protein does generate the same green GFP emission as in vivo . Stopped‐flow experiments, one using this fusion protein as well more recently, clytin and Clytia GFP in free solution, revealed that in the course of the <10 ms rise time of the bioluminescence after Ca 2+ addition, the efficiency of bioluminescence FRET measured by the 510/470 nm intensity ratio increased at the same rate as the rise of bioluminescence intensity . This intriguing phenomenon of “GFP‐FRET” is a rich subject for a productive physical–chemical study (… the “Endless Frontier”).…”
Section: Firefly and Coelenterazinementioning
confidence: 91%
“…In this bioluminescent-fluorescent system GFP shifts the blue light produced by Aequorin to longer wavelengths, i.e. green light (Eremeeva, Van Berkel & Vysotski, 2016). Various bioluminescent-fluorescent systems have been developed in jellyfish (Fourrage et al, 2014).…”
Section: Functions Of Fluorescencementioning
confidence: 99%